Carcass characteristics of beef cattle males intact or castrate at different ages - Restle, João; Grassi, Celso; Feijó, Gelson Luís Dias (Pesquisa Agropecuaria Brasileira, 1994)
Sixty-five crossbred Charolais x Zebu males were divided into the following treatments: T1. castration at 1,5 month of age; T2. castration at eight months; T3. castration at 12 months and T4. intact males. A knife was used for castration. After a 24 hours chill, metric measurements were taken from the carcasses. Age at castration did not affect (P > .05) the carcass characteristics evaluated. Intact males showed higher slaughter and hot carcass weights than the castrated at 1,5 month (P < .05), not differing from T2 and T3. Carcass length was greater (P < .05) for the intact males. Males castrated at 1,5 month of age had carcasses with lower arm perimeter and worse conformation than the intact males. External fat was lower (P < .05) for the intact male carcasses. It can be concluded that the intact males showed higher carcass weight and better conformation score than the males castrated at young age, however, are deficient in external fat cover.